MANAJEMEN SARANA DAN PRASARANA PONDOK PESANTREN DALAM PERSFEKTIF ISLAM - Aziz, Nur; Muslim, Khidayat; Nurahmayanti, Annisa; Hidayat, Yayat (Universitas Tanjungpura, 2024)
The facilities and infrastructure of Islamic boarding schools are crucial aspects that need attention. This is because they influence the learning process and the comfort of students residing in the boarding schools. Comfort in teaching and learning activities greatly affects the success of the educational process in Islamic boarding schools. This research employs a library research approach. The data collection technique used involves seeking information on relevant variables such as records, books, papers, articles, journals, and so on. The research results indicate that, from an Islamic perspective, management refers to the concept of regulation as commanded by Allah in the Qur'an. The concept of facilities and infrastructure management in Islamic boarding schools from an Islamic perspective is clarified through explanations about the processes of planning, procurement, distribution, maintenance, inventory, and disposal of facilities and infrastructure in Islamic boarding schools. This article also discusses the Islamic view on the importance of managing the facilities and infrastructure of Islamic boarding schools, as depicted in the Qur'an and Hadith. Therefore, Islamic boarding schools must pay attention to these aspects, especially with the existence of the Education Management Information System (EMIS), which is useful for managing data on students, teachers, and facilities and infrastructure.